Overexpression of c-myc is associated with adverse clinical features and worse overall survival in multiple myeloma. Issue 11 (1st November 2016) - Szabo, Agoston Gyula; Gang, Anne Ortved; Pedersen, Mette Ølgod; Poulsen, Tim Svenstrup; Klausen, Tobias Wirenfeldt; Nørgaard, Peter
Abstract: The role of c-myc in multiple myeloma (MM) is controversial. We conducted a retrospective study of 117 patients with MM diagnosed between 2004 and 2010 at Herlev Hospital. Immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) were performed on tissue microarrays (TMAs) made from diagnostic bone marrow aspirates. Clinical data were obtained from the Danish Multiple Myeloma Database (DMMD). Overexpression of c-myc was found in 40% of patients. MYC translocation was found in 10% of patients. Overexpression of c-myc was not associated with MYC translocation. Overexpression of c-myc was associated with hypercalcemia ( p  = 0.02) and extramedullary myeloma ( p  < 0.01). Overexpression of c-myc was associated with shorter overall survival (OS) by multivariable analysis of the entire patient cohort [HR 1.92 (1.06–3.45), p  = 0.03] and univariable analysis of high-dose-therapy (HDT)-ineligible patients [HR 2.01 (1.05–3.86), p  = 0.04]. Further studies of c-myc overexpression in larger cohorts of patients with MM are warranted.